PENGARUH APLIKASI NILAI-NILAI AL-ISLAM DAN KEMUHAMMADIYAHAN TERHADAP PEMAHAMAN AKUNTANSI - mursakinah, mursakinah; Rahim, Abd Rahman (Universitas Muhammadiyah Makassar, 2018)
This study aims to determine the effect of the application of Al-Islam and Kemuhammadiyahan values on the understanding of accounting for alumni of the accounting study program at Unismuh Makassar. Samples used in this research was alumni of the 2010 class of accounting study program at the University of Muhammadiyah Makassar. The number of questionnaires distributed was 86 questionnaires and only 64 questionnaires were used. The type of research used in the study was a case study study with an approach quantitative descriptive statistics. The data is processed using simple linear regression analysis with the SPSS 20.00 program. The results showed that the application variables of Al-Islam and Kemuhammadiyahan values had a significant effectpositive for Understanding Accounting in Unismuh accounting alumniMakassar.